A tissue-level phenome-wide network map of colocalized genes and phenotypes in the UK Biobank - Ghislain Rocheleau; Iain S. Forrest; Áine Duffy; Shantanu Bafna; Amanda Dobbyn; Marie Verbanck; Hong-Hee Won; Daniel M. Jordan; Ron Do (Communications Biology, 2022)
A phenome-wide genomic analysis on the UK Biobank cohort links >9,000 co-localized genes and >1,400 human phenotypes across a broad selection of human tissues, representing a useful resource for the investigation of relationships between gene expression, tissues, and human diseases.